Procesy elektronizacji w spółkach kapitałowych. Stan obecny a perspektywa najbliższych zmian - Mroczyński-Szmaj, Łukasz (PRAWO i WIĘŹ, 2025)
This article is an attempt at systematising the phenomenon of electronisation, primarily in the light of major changes in the area of digital revolution, particularly concerning corporations. The author expresses confidence about relevance of electronisation procedures, while highlighting the fact that they cannot lead to discrimination and exclusion in relation to the disappearance of the traditional form. The review carried out in the article is a rare attempt at looking “at once” at all dynamic electronisation processes which had accelerated significantly over the last 5 years, as a result of the COVID-19 pandemic. Among the necessary changes to legislation, the author postulates the need for improving the safety of electronic signatures and the increasingly common contribution of notaries in electronisation processes in corporations.